Pembelajaran Materi Bernyanyi Solo Di Kelas IX SMP Pertiwi 2 Padang - Ridha Hamdani; Jagar Lumbantoruan (Jurnal Mahasiswa Kreatif, 2023)
Learning material for solo singing at SMP Pertiwi 2 Padang has been carried out according to the students' abilities with designs planned by the teacher. Learning to sing solo is an activity that trains singing skills in accordance with breathing skills, resonance, mastering the melody, pronunciation, breaking up song sentences and expressions. In singing solo there are no problems faced by students as students and teachers as educators. The problems that often occur are the time dimension, space dimension and melody which are often not harmonious so that students' abilities are very limited, due to a learning tradition in the form of imitating what the teacher does which is what the students emulate. Learning to sing solo at SMP Pertiwi 2 Padang, to be precise in class IX, the teacher carries out learning to sing solo using an unclear method. The method is a method used by educators in front of students to achieve learning objectives well, but after the researcher observes the end of the lesson, the students are asked by the teacher to sing a song. The time dimension and space dimension are not harmonious. Then there is a tendency that it is doubtful that solo singing learning will not be as expected which depends on 3 things, how the teacher designs the RPP, KD and IPKD which are not yet relevant and the lesson material is not developed according to the expected development.